To build a home: A phenomenological approach of reconstructing “feeling-at-home” among children living in households with parents exhibiting depressive symptoms - Yap, Joseph Sebastian (Archīum Ateneo, 2020)
Living in a household with a parent exhibiting depressive symptoms causes major disruptions in family relations, particularly between parent and child, and radically changes family life spaces. In this study, we integrated a place-based approach to interpretative phenomenological analysis to examine the subjective experiences of “feeling-at-home” among children living in households with parents exhibiting depressive symptoms. Using accounts obtained from photo elicitation interviews with seven participants, four key findings show the experience of “feeling-at-home” as (1) navigating emotional turmoil evoked through black holes and comfort rooms, (2) managing “being together” evoked through walls and dining tables, (3) overcoming fear evoked through terraces and flowers, and (4) seeing hope in what is (left of) home (somewhere). Main discussion highlights the spatial constitution in phenomenological research, children’s agency within volatile and “immovable” households, and changing spaces of emotional scarring.